Partisipasi Masyarakat Dalam Melestarikan Tradisi Sayyang Pattudu di Desa Sidorejo Kecamatan Wonomulyo Kabupaten Polewali Mandar - Mudfainna; Abdul Halik; Hasruddin Nur (Universitas Islam Negeri Alauddin Makassar, 2023)
The type of research used is ethnographic research and uses a qualitative and sociological approach. Data collection is done by observation, interviews, and documentation. Sources of data in this study were obtained from two sources, namely primary data sources from 6 (six) informants and secondary data sources from relevant documents. Then the data analysis technique is carried out in three stages, namely: data reduction, data presentation and drawing conclusions. The results showed that the Sayyang Pattu'du tradition is a traditional Mandar performance held to appreciate children who have memorized the Koran by parading around the village on a horse and accompanied by tambourine music and Mandar poetry (kalindaqdaq), and there is a passarung as a companion. maintain the balance of the rider and the palangi who is in charge of holding the umbrella so that the rider does not overheat. In preserving the sayyang pattu'du tradition, there is community participation. Forms of community participation include: the planning stage, the implementation stage and the utilization stage. After going through these stages, there are types of participation of the Sidorejo Village community in preserving the sayyang pattu'du tradition, including: 1) Mind participation, 2) Energy participation, 3) Money participation, and 4) Emotional participation. The preservation efforts are: 1) Carrying out the sayyang pattu'du tradition every year, 2) Not changing the procedures for implementation, and 3) Collaborating with all parties.